Preoperative Cardiac Evaluation of Adult Patients Undergoing Noncardiac Surgery in Nepal: Multidisciplinary Consensus Recommendations from a Modified Delphi Study - Sharma, Apurb; Panta, Sukirti Baba; Parajuli, Bashu; Shrestha, Ravi Ram; Shrestha, Battu Kumar; Ghimire, Bikal; Joshi, Anip; Mukhiya, Rupesh; Raut, Roshan; Singh, Amit Kumar; Lakhe, Gajal; Sah, Ram Kishor; et al. (Nepalese Heart Journal, 2025)
Background: Cardiac complications remain a major cause of perioperative morbidity and mortality globally among patients undergoing noncardiac surgery. In Nepal, implementing international guidelines is challenging due to resource constraints, workforce variability, and a high burden of rheumatic heart disease, early-onset coronary artery disease and chronic obstructive pulmonary diseases. Objective: To develop standardized, evidence-based recommendations for preoperative cardiac evaluation for adult patients undergoing noncardiac surgeries focussed on Nepalese context. Methods: Cardiac Society of Nepal coordinated a three-round modified Delphi process amongst cardiologists, anesthesiologists, and surgeons from healthcare institutions across Nepal. The AGREE II framework guided guideline development, and DELPHISTAR standards ensured transparent reporting. Consensus was defined as ≥70% "Strongly Agree" or ≥80% "Strongly Agree + Agree". Results: Consensus was achieved on 26 key recommendations covering screening, risk stratification, prehabilitation, surgical and institutional considerations. These recommendations adapt international best practices to Nepal’s specific challenges, prioritizing low cost tests like ECG, selective use of echocardiography and biomarkers, and addressing modifiable risk factors preoperatively. Conclusion: This multidisciplinary consensus provides a context-appropriate, pragmatic framework for preoperative cardiac evaluation in Nepal. It aims to improve perioperative outcomes, support coordinated perioperative care, and guide national perioperative quality standards and future research.